ISSUES OF USE OF INFORMATION TECHNOLOGIES IN IMPROVING THE QUALITY OF SEMINAR LESSONS IN HIGHER EDUCATION - Zohidova Mahfuza Xabibovna (Galaxy International Interdisciplinary Research Journal, 2022)
The article describes the systematic use information-communication technologies in the activities of educational institutions, the importance of effective application of modern technologies, the significance of approbation and regular implementation of benefiting from the possibilities of manuals and facilities, the processes of using the information-communication technologies.